Angiographic Characteristics of Renal Dysfunction Patients Presenting With Non–ST Elevated Acute Coronary Syndrome (University Heart Journal, 2026)
Background: Chronic kidney disease (CKD) is increasingly recognized as an important and independent risk factor for cardiovascular disease. Patients with CKD frequently present with acute coronary syndromes (ACS) and demonstrate worse short- and long-term outcomes compared with those with preserved renal function. Non–ST elevation acute coronary syndrome (NSTE-ACS) represents a heterogeneous clinical spectrum, and renal dysfunction significantly influences disease severity, treatment decisions, and prognosis.Objectives: To evaluate and compare the coronary angiographic characteristics of patients presenting with NSTE-ACS with and without chronic kidney disease.Methods: This prospective observational study included 60 consecutive patients diagnosed with NSTE-ACS and admitted to the Department of Cardiology, Bangladesh Medical University, between December 2024 and December 2025. Patients were divided into two groups based on estimated glomerular filtration rate (eGFR): CKD group (eGFR